298 AN AUDIT OF HEALTH PROFESSIONALS' KNOWLEDGE OF PARKINSON'S DISEASE AND ITS MEDICATION MANAGEMENT FOR HOSPITALISED PATIENTS. (25th October 2022) - Connolly, E; Reidy, C; Murphy, A; Pope, G; Cooke, J; Bambrick, P; O'Regan, N; Mulcahy, R
Abstract: Background: Studies have shown that patients with Parkinson's Disease (PD) have a higher rate of hospitalisation and longer lengths of stay than their age matched controls. Good inpatient management is key to maintaining functional ability and preventing complications, but many PD patients deteriorate while in hospital. Patients with PD are often on multiple time sensitive medications. This study aims to assess healthcare workers knowledge of PD, medications used to treat it and how they should be prescribed and administered. Methods: A convenience sample survey was distributed to doctors, nurses and other health care professionals over a five-week period. This survey included multiple choice questions and open-ended short answer questions. Results were collated and analysed on Microsoft Excel. Results: 71 surveys were returned - 34 from doctors, 23 from nurses and the 14 others included pharmacists, physios and dieticians. Only 11 (15%) participants correctly identified all PD medications listed in the survey with Sinemet being the most recognised drug (n= 68). Non motor symptoms of PD correctly identified by participants included constipation (n=54, 76%), hallucinations (n=48, 68%) and anosmia (n=18, 25%). 32 participants (45%) were unable to correctly identify when to administer PD medications in relation to mealtimes. 29 participants surveyed (41%) would consider inserting a nasogastric tube for a patient who was fasting and unable to take oral medications. 12 participants (17%) did not know that Sinemet could be given via nasogastric tube. Conclusion: This survey highlights a gap in knowledge of Parkinson's Disease and its management. Participants displayed poor knowledge regarding optimum timing of medication administration and management of patients who are fasting. These findings suggest that education sessions and hospital specific guidelines regarding the management and administration of PD medications would assist healthcare professionals with a view to improving patient outcomes and preventing complications.